Cytotoxic activity of ethyl acetate extract of Chromolaena odorata on MCF7 and T47D breast cancer cells - Yusuf, Hanifah; Novia, Hijra; Fahriani, Marhami (Narra J, 2023)
One of the most cancers in women that can be fatal is breast cancer. Radiation therapy, chemotherapy, or a combination of the two are often used to treat cancer, and these treatments tend to modify the immune system and weaken defences. Using natural compounds from plants has become a research interest to prevent cancer cell development. The aim of this study was to determine the anticancer activities of ethyl acetate extract of Chromolaena odorata (EACO) against breast cancer cells (MCF-7 and T47D). The viability of the cells was determined by the MTT colorimetry assays. The apoptosis test was performed by using flow cytometry. The IC50 value for MCF-7 cells was 218.78 μg/mL and 307.61 μg/mL for T47D. The extract acted selectively against breast cancer cells, with selectivity indexes against MCF-7 and T47D were 12.77 and 9.08, respectively. The viable cells of T47D cells were decreased from 85±36.5% (24 hours) to 54±34% (48 hours) after treatment with IC50 of EACO. Significant decrease of the MCF-7's viable cells were observed between 48 and 72 hours after treatment with IC50 (68.5±17.7% to 51.01±12.1%, respectively). Apoptosis assay showed that T47D and MCF-7 cells were mainly in the necrosis stage (83.35±0.49% and 95.15±1.76%, respectively). This study suggested that ethyl acetate extract of C. odorata is promising to be developed as an anticancer agent.